Heroic Paradigms in the So-Called "Ilias Latina" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2025)
The so-called Latin Iliad represents a very interesting case-study in terms of intertextuality. Scholars – who already analyzed its effective literary value, justifying it with the lack of experience of an author commonly considered a beginner –, found in the poem some significant elements in connection with the representation of main characters. This article aims to offer a general overview of the characterization of the four most famous heroes (Achilles, Telamonian Ajax, Hector and Ulysses), in order to show how each one – even in function of the typical homeric hierarchy – could provide relevant points because of the presence of many variations and of the coexistence between different mythological traditions. As a result, the study seems to point out an overall operation that – in spite of objective limits – should be evaluated in a positive manner: it reveals a strong literary awareness, especially in consideration of cultural context of the Neronian age.
Keywords: : Latin Iliad, Achilles, Ajax, Hector, Ulysses; Latin Iliad; Achilles; Ajax; Hector; Ulysses